Self-Regulation Failure? The Influence Mechanism of Leader Reward Omission on Employee Deviant Behavior - Wang, Tian; Cao, Zhoutao; Zhong, Xi; Chen, Chunhua (Frontiers in Psychology, 2021)
Contingent reinforcement behavior is generally regarded as one of the key elements of being a “good” leader, yet the question of what happens when this behavior is absent has received little attention in past empirical research. Drawing upon self-regulation theory, we develop and test a model that specifies the effects of leader reward omission on employes’ deviant behavior. Using the data of 230 workers from two manufacturing companies located in South China collected across three time points, we find that leader reward omission is positively associated with deviant behavior. Moreover, the indirect effects of leader reward omission on employes’ deviant behavior are mediated by moral disengagement. Our study also reveals that Machiavellianism can aggravate the positive effect of leader reward omission on moral disengagement, and subsequently exacerbate the indirect effect on employes’ deviant behavior. Taken together, our findings reveal the consequences of leader reward omission, and the importance of examining subordinate self-regulation under the lack of positive reinforcement.